The Relationship Between Body Mass Index, Physical Activity, Nutritional Intake With Physical Fitness Of KKO Students In Bantul Regency - Ilham Cahyana Jati; Hermawan, Hedi Ardiyanto; Ngatman, Ngatman (Indonesian Journal of Sport Management, 2025)
Background: Write down the background/context of the research along with the research gaps. Write down the background/context of the research along with the research gaps. Purpose: This study aims to determine the relationship between body mass index, physical activity, nutritional intake with the level of physical fitness of special sports class students in Bantul Regency. Methods: The type of research used is correlation research with bivariate correlation research design. Population and research samples of special sports class students in Bantul Regency with a total of 110 students. The sampling technique used total sampling technique. Results: The results showed that the Body Mass Index of students of special sports classes in Bantul Regency was in the normal category with an average of 19.95. The results of the analysis of the relationship between physical activity and physical fitness obtained the price of Tcount = 0, 166 with Ttable = 0, 451, thus there is no significant relationship between physical activity and the level of physical fitness of students of special sports classes in Bantul Regency. The results of the analysis of the relationship between nutritional status and physical fitness level obtained the price of Tacount = 0.144 with Table = 0.451. Conclusion Thus it can be concluded that there is a relationship between BMI and the level of physical fitness = rcount 0.300 and rtable (df 55; 0.05) 0.260 with a Sig value. 0.023 <0.05, then H0 is rejected and Ha is accepted, which means that if there is a relationship then the relationship is significant between the independent variable and the dependent variable, with a low correlation relationship, there is no significant relationship between nutritional status and the level of physical fitness of students of special sports classes in Bantul Regency. Implications and Recommendation: These results indicate that physical activity and nutritional status have no effect on physical fitness, because the pandemic transition causes physical activity and nutritional status with fitness there is no relationship. maintain a eating pattern and balanced with frequent daily activities in order to create normal body shape and good physical fitness.